BioEssays 4/2020. (19th March 2020) - Dragani, Tommaso A.; Matarese, Valerie; Colombo, Francesca
Abstract : Enormous efforts and resources are being invested in the search for biomarkers for early cancer detection. However, the biology and genetics of cancer, an extremely heterogeneous disease from the molecular viewpoint, thwart the clinical application of laboratory discoveries, and the sought‐for pan‐cancer biomarkers for population screening remain out of reach. Notwithstanding advances made using artificial intelligence to overcome current limitations in cancer biomarker research, in article number 1900122, Tommaso A. Dragani et al. speculate that there is still a long way to go before this important public health goal is achieved.